IN VITRO EVALUATION OF SELECTED PLANT EXTRACTS ON THE MYCELIAL GROWTH OF SCLEROTIUM ORYZAE CATT,. - N.VENKATESWARLU; A.SREERAMULU (International Journal of Pharma and Bio Sciences, 2013)
Stem rot is important disease of paddy (Oryza sativa) causing significant reduction in yield. In this present study the pathogenic fungi was isolated from infected plant parts and in vitro efficacy of different plant extracts viz., Nyctanthes arbor-tristis, Strychnos nux-vomica, Wrightia tinctoria, Syzygium cumini, Ocimum tenuiflorum were tested to control stem rot pathogen. Different concentrations of plant extracts were used in the study. All the plant extracts showed significant reduction in the growth of pathogen. Among the different extracts 2% of Nyctanthes arbor-tristis was found effective followed by Strychnos nux-vomica, Wrightia tinctoria, Ocimum tenuiflorum and Syzygium cumini. Application of plant extracts which are easily available for controlling plant diseases are cost effective and eco-friendly. Further investigations are in progress to test the efficacy of these extracts in field applications.